1998
DOI: 10.1590/s0102-311x1998000700008
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and occupational cancer in Argentina: a case-control lung cancer study

Abstract: The main objective of this study was to analyze the risks for lung cancer associated with occupational exposures in a developing country where lung cancer is the first cause of mortality from cancer in men. The study involved 200 men with lung cancer and 397 hospital controls. The OR for current smokers was 8.5, whereas former smokers displayed an OR of 5.3. The fraction attributable to smoking was 85%. Statistically significant high ORs were observed for employment in the alcoholic beverages industry (4.5, 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Smoking is one of the main causes of lung cancer worldwide [16]. 85% of cases of lung cancer in men are related to smoking [97]. In 2004, lung cancer includes 18% of all types of cancers, of which 938,000 mortality (71%) were related to smoking [57].…”
Section: Cigarette Smokingmentioning
confidence: 99%
“…Smoking is one of the main causes of lung cancer worldwide [16]. 85% of cases of lung cancer in men are related to smoking [97]. In 2004, lung cancer includes 18% of all types of cancers, of which 938,000 mortality (71%) were related to smoking [57].…”
Section: Cigarette Smokingmentioning
confidence: 99%
“…Although in our study we could not differentiate vehicle mechanics from others, we observed a slightly increased mortality from lung cancer in non-white mechanics in the South region. However, the mechanic occupation has been inconsistently associated with lung cancer, as some '80s and '90s studies have shown positive associations (Zahm et al, 1989;Matos et al, 1998;Milne et al, 1983;Finkelstein, 1989), while recent studies have not confirmed it (Goodman et al, 2004;Garshick et al, 2008;Strand et al, 2015;Laden et al, 2004). Benzene is one of the most well stablished environmental risk factor for acute myeloid leukemia (IARC, 2018).…”
Section: Discussionmentioning
confidence: 99%